Analysis of Cashback Marketing Content to Increase Business Competitiveness Through the Electronic Trading Company Marketplace: Analisis Konten Pemasaran Cashback Guna Meningkatkan Daya Saing Bisnis Melalui Marketplace Perusahaan Perdagangan Elektronik - Nasrudiansyah, Dicky Septian; Sukmono, Rita Ambarwati (Indonesian Journal of Innovation Studies, 2023)
The nature of writing this research has the first purpose to map the interactions and structures that occur among tokopedia consumers on social media twitter, the second to find out strategy recommendations digital marketing on tokopedia marketplace processed using methods social network analysis. Today's global civilization, manufacturing activities are beginning to witness tremendous changes in various countries. With the emergence of information technology and its increasingly advanced convenience, we all have the ability to think creatively in the face of more and more competition, the most important thing in the era of Covid-19 is the decline of the world economy. Business actors are expected to continue to think and be creative in order to improve, advance and maintain their business in order to obtain maximum profits and be known to the wider community. This research is qualitative descriptive research using data Secondary derived from Twitter. Methods used in this study Using the Social Network Analysis (SNA) method by using big data. In data retrieval assisted by a variety of tools. The support that will be used in this research is Google Colab, Jupyter Colab, Dictionary, Wordij and Gephi.